Comparative Analysis of (HF) Non-Linear Circuits Modelled by Different Environments - Dobrucky, B.; Benova, M.; Frivaldsky, M.; Radvan, R.; Gombarska, D. (Elektronika ir Elektrotechnika, 2013)
Many electric circuits feature some type of non-linearity of their used devices. Non-linear resistors or inductors could be typical examples. Also, all semiconductor devices are in their nature non-linear ones. From the point of view of the circuit solution they are presented non-linear static and dynamical system described by differential equations. Particularly, in steady state, it could be system of non-linear algebraic equations. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1754